Manajemen Ekstrakurikuler Tahfidzul Qur’an di MTs YPI Subulul Huda Saentis, Percut Sei Tuan, Kab. Deli Serdang - Neliwati; Nursela Anggraini; Suheri, Muhammad; Icha Puspita Sari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to obtain information and a clear picture about Tahfidzul Qur'an Extracurricular Management at MTs YPI Subulul Huda Saentis, Percut Sei Tuan, Deli Serdang Regency. The focus of the research study in this research is how the Tahfidzul Qur'an Extracurricular Management is carried out at the school. The research method used is the type of research carried out is qualitative research. The approach in this research uses a phenomenological approach. The techniques used are observation, interviews and documentation. Data analysis using the Miles and Huberman technique explains that there are three methods in qualitative data analysis, namely data reduction, data presentation and conclusion/verification. The research results explain that (1) Planning for Tahfidzul Qur'an Extracurricular Activities consists of several stages of activity planning, namely setting goals, formulating goals and objectives, planning activity time, as well as suggestions and costs for implementation. (2) The organization of extracurricular activities is detailed based on their respective duties, namely the principal is in charge of the activities, the deputy principal for student affairs is the supervisor, the extracurricular coordinator is the person who coordinates and the extracurricular supervisor is to carry out training and teaching to each member of the Tahfiz Qur 'an. (3) Tahfidzul Qur'an extracurricular activities are carried out outside learning hours. (4) Supervision of Tahfidzul Qur'an Extracurricular Activities is carried out directly or indirectly or at the end of the activity.